EXPERIMENTS ON THE KINETICS OF PARTIAL MELTING OF A LEUCOGRANITE AT 200 MPA H2O AND 690–800°C: COMPOSITIONAL VARIABILITY OF MELTS DURING THE ONSET OF H2O-SATURATED CRUSTAL ANATEXIS - Acosta-Vigil A.; London D.; Morgan G.B. (My University, 2006)
We have experimentally investigated the kinetics of melting of an aplitic leucogranite (quartz+sodic plagioclase of ≈Ab90+K-feldspar+traces of biotite) at 690, 740, and 800°C, all at 200 MPa H2O. Leucogranite cylinders, 3.5 mm in diameter and 7 mm in length, were run in the presence of excess H2O using cold-seal pressure vessels for 11–2,925 h. At 690 and 740°C and any experimental time, and 800°C and short run times, silicate glass (melt at run conditions) occurs as interconnected films along most of the mineral boundaries and in fractures, with the predominant volume occurring along quartz/feldspars boundaries and quartz/plagioclase/K-feldspar triple junctions. Glass film thickness is roughly constant throughout a given experimental charge and increases with experimental temperature and run duration. The results indicate that H2O-saturated partial melting of a quartzo-feldspathic protolith will produce an interconnected melt phase even at very low degrees (<5 vol%) of partial melting. Crystal grain boundaries are therefore completely occluded with melt films even at the lowest degrees of partial melting, resulting in a change in the mechanism of mass transport through the rock from advection of aqueous vapor to diffusion through silicate melt. At 690 and 740°C the compositions of glasses are homogeneous and (at both temperatures) close to, but not on, the H2O-saturated 200 MPa haplogranite eutectic; glass compositions do not change with run duration. At 800°C glasses are heterogeneous and plot away from the minimum, although their molar ratios ASI (=mol Al2O3/CaO+Na2O+K2O) and Al/Na are constant throughout the entire charge at any experimental time. Glass compositions within individual 800°C experiments form linear trends in (wt%) normative quartz–albite–orthoclase space. The linear trends are oriented perpendicular to the 200 MPa H2O haplogranite cotectic line, reflecting nearly constant albite/orthoclase ratio versus variable quartz/feldspar ratio, and have endpoints between the 800°C isotherms on the quartz and feldspar liquidus surfaces. With increasing experimental duration the trends migrate from the potassic side of the minimum toward the bulk rock composition located on the sodic side, due to more rapid (and complete) dissolution of K-feldspar relative to plagioclase. The results indicate that partial melting at or slightly above the solidus (690–740°C) is interface reaction-controlled, and produces disequilibrium melts of near-minimum composition that persist metastably for up to at least 3 months. Relict feldspars show no change in composition or texture, and equilibration between melt and feldspars might take from a few to tens of millions of years. Partial melting at temperatures well above the solidus (800°C) produces heterogeneous, disequilibrium liquids whose compositions are determined by the diffusive transport properties of the melt and local equilibrium with neighboring mineral phases. Feldspars recrystallize and change composition rapidly. Partial melting and equilibration between liquids and feldspars might take from a few to tens of years (H2O-saturated conditions) at these temperatures well above the solidus.
Keywords: PARTIAL MELTING; INTERFACE REACTION; TRIPLE JUNCTION; MELTING REACTION; GLASS FILM